2013
DOI: 10.1002/jmri.24491
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic efficacy of the diffusion weighted imaging in the characterization of different types of breast lesions

Abstract: Despite the lower diagnostic accuracy of DWI in NMEs, it could be helpful in the characterization of suspicious breast lesions of both mass and NME types.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 28 publications
(45 reference statements)
2
25
0
Order By: Relevance
“…For these reasons, measurement of ADC across the entire visible region of restricted diffusion are likely to be more reproducible than ADC min , particularly in follow up studies, even if potentially important information on tumor heterogeneity is obscured. Currently there is no consensus as to whether ADC values should be averaged across the lesion area on one slice or minimum ADC values within a lesion should be reported and there are a number of studies reporting both methods [21][22][23][24]. Studies reporting ADC min used various ROI sizes, with some reporting only minimum pixel value.…”
Section: Discussionmentioning
confidence: 97%
“…For these reasons, measurement of ADC across the entire visible region of restricted diffusion are likely to be more reproducible than ADC min , particularly in follow up studies, even if potentially important information on tumor heterogeneity is obscured. Currently there is no consensus as to whether ADC values should be averaged across the lesion area on one slice or minimum ADC values within a lesion should be reported and there are a number of studies reporting both methods [21][22][23][24]. Studies reporting ADC min used various ROI sizes, with some reporting only minimum pixel value.…”
Section: Discussionmentioning
confidence: 97%
“…However, we had fewer large tumors in our study compared with that of Razek et al In addition, the low b‐values of 200 and 400 s/mm 2 used in their study could have affected the results. Kul et al recently reported that ADC values of the masses were independent of size.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, previous studies using different scanning parameters reported different cutoff values for the discrimination of malignant and benign tumors (13,(21)(22)(23). In our practice, we routinely apply DWI as a part of our standard breast MRI protocol and as ADC threshold we use 0.90 ×10 -3 mm 2 /s, which is the cutoff value that was obtained from our previous DWI study (15). We also used this cutoff value in our present prospective study, and it provided good discrimination between malignant and benign masses.…”
Section: Discussionmentioning
confidence: 99%
“…At least three measurements were performed for each mass and the lowest mean value was selected. We used 0.90×10 -3 mm 2 /s as the ADC cutoff value that was obtained from our previous DWI study of 285 cases (124 benign and 161 malignant tumors) (15).…”
Section: Image Analysismentioning
confidence: 99%